2004
DOI: 10.1016/j.febslet.2004.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of nuclear pore complex proteins in gp210 deficient cells

Abstract: Gp210, an integral membrane protein of the nuclear pore complex (NPC), is believed to be involved in NPC biogenesis. To test this hypothesis, we have investigated dynamic properties of the NPC and distribution of NPC proteins in NIH/ 3T3 cells lacking gp210. POM121 (the other integral NPC protein) and NUP107 (of the NUP107/160 complex) were correctly distributed at the nuclear pores in the absence of gp210. Furthermore, fluorescence recovery after photobleaching experiments showed that POM121 and NUP107 remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Countering this by using shRNA-mediated inhibition of Nup210, we showed that MEFs fail to reprogram in the absence of Nup210 (Figure 6). Interestingly, earlier observations have indicated that Nup210 is dispensable for nuclear pore complex assembly (Eriksson et al, 2004; Stavru et al, 2006), showing preferred expression in epithelial cells while absent in mesenchymal cells, including fibroblasts (Eriksson et al, 2004; Olsson et al, 2004; Stavru et al, 2006). In spite of low expression of Nup210 in MEFs (Figure S4), we observed that its repression resulted in inhibition of cellular proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Countering this by using shRNA-mediated inhibition of Nup210, we showed that MEFs fail to reprogram in the absence of Nup210 (Figure 6). Interestingly, earlier observations have indicated that Nup210 is dispensable for nuclear pore complex assembly (Eriksson et al, 2004; Stavru et al, 2006), showing preferred expression in epithelial cells while absent in mesenchymal cells, including fibroblasts (Eriksson et al, 2004; Olsson et al, 2004; Stavru et al, 2006). In spite of low expression of Nup210 in MEFs (Figure S4), we observed that its repression resulted in inhibition of cellular proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Of the three human integral membrane nucleoporins, POM121, Ndc1, and gp210, the first two have a very small lumenal presence (33–39 aa and 21–30 aa) (Hallberg et al , 1993; Lau et al , 2006). Gp210 has a large lumenal domain (1782 aa) (Gerace et al , 1982), but has been found to be dispensable in some studies, both by RNAi depletion and in certain cells that naturally lack gp210 (Wozniak et al , 1989; Greber et al , 1990; Hallberg et al , 1993; Cotter et al , 1998; Drummond and Wilson, 2002; Liu et al , 2003; Eriksson et al , 2004; Olsson et al , 2004; Antonin et al , 2005; Lau et al , 2006; Mansfeld et al , 2006; Stavru et al , 2006a). Thus, neither Pom121, Ndc1, nor gp210 appears on its own to fill the requirements for bridging the lumenal gap needed for inner/outer membrane fusion.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, only three transmembrane Nups have been identified: POM121, gp210, and Ndc1 (Chial et al, 1998; Hallberg et al, 1993; Mansfeld et al, 2006; Stavru et al, 2006b). While gp210 is not expressed in all cell types (Eriksson et al, 2004) and thus unlikely to play a role in NPC biogenesis, RNAi-mediated silencing of POM121 and Ndc1 has been shown to negatively affect NPC assembly (Antonin et al, 2005; Mansfeld et al, 2006; Stavru et al, 2006a; Stavru et al, 2006b). Furthermore, the appearance of POM121 has been shown to be an early step in NPC assembly both in vivo and in vitro (Dultz et al, 2008; Rasala et al, 2008), and essential for NE formation in vitro (Antonin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%